THE EFFECT OF PRODUCT QUALITY AND SECONDATE BEAUTY BRAND IMAGE TOWARDS CONSUMER REPURCHASE INTENTION - Dezila, Raissa; Ariyanti, Maya (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
Based on BPS data in the first quarter of 2020, pharmaceutical growth, chemical industry, traditional medicine including cosmetics grew 5.59%. With this phenomenon, entrepreneurs in the country are interested in entering the cosmetic industry. One of them was Secondate Beauty, which issued its first product, Milky Gel Lip Tint. This product has received numerous reviews, both positive and negative. The purpose of this study is to determine the impact of product quality and brand image on the desire to repurchase Secondate Beauty cosmetics. Data collection in this study will be processed by spreading questionnaire and will be analyzed by SmartPLS 3.3.5. The results show that all variables in this study have a significant influence on the intensity of Secondate Beauty consumers in repurchasing.